2018
DOI: 10.1002/jcp.26601
|View full text |Cite
|
Sign up to set email alerts
|

Thiostrepton degrades mutant p53 by eliciting an autophagic response in SW480 cells

Abstract: Mutations in p53 gene are one of the hallmarks of tumor development. Specific targeting of mutant p53 protein has a promising role in cancer therapeutics. Our preliminary observation showed destabilization of mutant p53 protein in SW480, MiaPaCa and MDAMB231 cell lines upon thiostrepton treatment. In order to elucidate the mechanism of thiostrepton triggered mutant p53 degradation, we explored the impact of proteasome inhibition on activation of autophagy. Combined treatment of thiostrepton and cycloheximide/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Luo et al claimed that, under sunitinib treatment, p62 could directly bind to p53 for its autophagic degradation with the help of HMGB1 [ 25 ]. Kalathil et al performed interactome analysis and revealed an association of p53 with autophagosome complex associated proteins including BAG3, p62 and HSC70 under thiostrepton treatment [ 28 ]. We explore the relationship between p62 and p53 signaling pathway and the results indicate that p62 associates with p53, inhibits the ubiquitination of p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al claimed that, under sunitinib treatment, p62 could directly bind to p53 for its autophagic degradation with the help of HMGB1 [ 25 ]. Kalathil et al performed interactome analysis and revealed an association of p53 with autophagosome complex associated proteins including BAG3, p62 and HSC70 under thiostrepton treatment [ 28 ]. We explore the relationship between p62 and p53 signaling pathway and the results indicate that p62 associates with p53, inhibits the ubiquitination of p53.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, since p62 is the receptor protein for selective autophagy of ubiquitinated cargos, is it possible that autophagy involved in the regulation of our study? As previous literature described, p62 may deliver or interact with p53 for its autophagic degradation under certain stress [ 24 , 25 , 28 ]. Does p62 inhibit the ubiquitination of p53 in proteasome-dependent way or in autophagy-dependent pathway?…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro evidence has demonstrated the significant anticancer effects of TST ( 11 ). By targeting FoxM1 protein and the proteasome, TST induces cell apoptosis in ovarian and lung cancer, as well as in other types of tumor cells ( 13 15 ). As a novel anticancer target, TST has been extensively studied in tumor research ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Select thiopeptides also have effects on mammalian cancer cells and macrophages. , TSR in particular interacts with several mammalian targets, including the oncogenic transcription factor, Forkhead box M1 (FoxM1), and the 26S proteasome, both of which could potentially be leveraged for anticancer chemotherapy (Figure B, pathways 1 and 2). , Recently, TSR was also shown to induce macroautophagy (hereafter referred to as autophagy) in macrophages. , Autophagy is a bulk intracellular degradation process in which cytoplasmic components are encapsulated in double-membrane bound vesicles (i.e., autophagosomes) and shuttled to lysosomes for degradation (Figure B, pathway 3). , Eukaryotic cells use autophagy for nonspecific processes, such as recycling cytosolic materials for nutrient homeostasis. Additionally, there are also cargo-specific forms of autophagy that target pathogens, damaged organelles (e.g., mitochondria, endoplasmic reticulum), or protein aggregates. ,, Selective autophagy of pathogens is a host defense against intracellular infections. Thus, the autophagy activity of TSR is enticing from an antibiotic development standpoint, and chemical inducers of autophagy are actively being investigated as host-directed therapeutics to enhance immune clearance of intracellular pathogens. , For Mtb specifically, a number of compounds that induce autophagy are shown to reduce the intracellular burden of Mtb . , A thorough understanding of the structural and mechanistic basis of the host-directed activities of TSR and cognate thiopeptides, as well as their contributions to intracellular bacterial clearance, will benefit further antibiotic development.…”
mentioning
confidence: 99%